PENGARUH CONTENT MARKETING DAN BRAND IMAGE TERHADAP MINAT BELI MAFIA GEDANG DI KOTA SURABAYA - Adelia, Resha; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to examine the impact of Content Marketing and Brand Image on the Buying Interests of the Gedang Mafia in Surabaya City. The analytical method uses the IBM version of SPSS software 25. The results show that individually there is a positive influence between Content Marketing on purchase intention with a value of 3.646 > 1.984, and there is a positive influence between Brand Image and purchase intention with a value of 3.620 > 1.984. In addition, the results of the study also identified that overall there was a positive influence between Content Marketing, Brand Image and purchase intention with a value of 79.800 > 3.09. Research data were collected via google form and measured using a Likert scale with the help of SPSS software IBM version 25 and analyzed using multiple linear regression methods. The findings of this study indicate that partially there is a positive influence between Content Marketing and purchase intention, and there is a positive influence between Brand Image and purchase intention. In addition, the research results also explain that overall there is a positive influence between Content Marketing, Brand Image, and purchase intention. Keywords : Content Marketing, Brand Image, and Purchase Intention